Oribatula (Zygoribatula) propinqua - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Oribatula (Zygoribatula) propinqua (Oudemans, 1900) * Material – New record for Turkey. One specimen in Şahinler Natural Park, Ankara.Woody plants are represented by Pinus nigra, P. sylvestris L., Quercus sp., Fagus sp., N 40° 61′ 74.65′′, E 32° 45′ 55.46′′, alt. = 1660 m, 16 June 2018, soil with moss. Global distribution – Palaearctic. Ecology – On the trees, rare in dry soils.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 265, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Oribatulidae; Arachnida; Animalia; Oribatula propinqua; Biodiversity; Sarcoptiformes; Oribatula; Taxonomy; 15. Life on land